CULTURE OF Strelitzia reginae IN DIFFERENT SUBSTRATES - GOSEK, Carlos Fernando; CARVALHO, Ruy Inacio Neiva de (Scientia Agraria, 2010)
The objective of this study was to determine growth and development of Strelitzia reginae cultivated in pots with substrates added with worm compost. The experiment was carried out at a greenhouse and the experimental design was a randomized block with a three factors scheme and three replications. The treatments consisted of two substrates (manufactured and commercial, Rendmaxâ), four doses of worm compost (0, 20, 40 and 60% of the total volume of the pot) and different times of evaluation, during 70 weeks for the vegetative growth and during 72 weeks for the production of inflorescences. The following parameters were evaluated: leaf area, leaves number, total leaf area of the plant, content of chlorophyll a, b and a + b, relation chlorophyll a/b, emission of inflorescences and substrate chemical alterations. The growth of S. reginae in the first 32 weeks in greenhouse was slow. The addition of worm compost in even 60% of the volume of the pot was favorable to the growth and development of S. reginae in the manufactured and commercial substrates.